Hak Politik Kaum Minoritas Towani Tolotang di Sulawesi Selatan - Qodir, Zuly (Unisia, 2018)
This article will give a description of the ethnographical border and political top minority citizens Group located in South Sulawesi, i.e. the believers Towani Tolotang that until now still esksis there even in the national political scene, contemporary Towani Tolotang ghosts because it has representatives in the legislature. The community seems to be playing politics Towani Tolotang accommodating and make use of what was to become the will of the political regime of Muslims and Hindus, where both of them are scrambling for mutual acknowledge and enter in the tradition of the religion: Islam or Hinduism. As citizens, communities have a variety of strategies Towani Tolotang which makes it able to survive and fight in the throes of various kinds of interest; as economic and political gain, as well as the commodification of ethnicity and religion were rampant in the area due to redistricting (decentralization). This article is based on field research and library for the past year dealing with political citizens pressed for by the large number of discriminatory treatment.